Anatomical and functional response after conversion to aflibercept using the treat-and-extend regimen protocol in bevacizumab treatment-resistant wet age-related macular degeneration - Taipale C (Dove Medical Press, 2018)
Claudia Taipale,1,2 Ilkka Laine,1,3 Raimo Tuuminen1,3 1Helsinki Retina Research Group, Medicum, Faculty of Medicine, University of Helsinki, Helsinki, Finland; 2Department of Ophthalmology, Helsinki University Hospital, Helsinki, Finland; 3Department of Ophthalmology, Kymenlaakso Central Hospital, Kotka, Finland Objective: To evaluate the functional and anatomical response after the switch from bevacizumab to aflibercept in treatment-resistant wet age-related macular degeneration (wAMD) using the treat-and-extend regimen protocol. Design: A retrospective single-center study. Participants: The registry consisted of 576 patients with wAMD. Of these, a total of 41 eyes of 37 patients met the study inclusion criteria with a minimum of three prior bevacizumab injections and at least 1-year follow-up after the switch to aflibercept injections for the treatment of wAMD. Methods: Central retinal thickness (CRT) and best-corrected visual acuity (BCVA) were recorded before and after bevacizumab loading phase, before the switch to aflibercept, after aflibercept loading phase, and after the last injection or at the study end point at a minimum of 1 year from the switch. Results: At the switch to aflibercept injections, the mean CRT was 361.1±117.7 µm (mean±SD) and BCVA was 0.29±0.19 decimals. The switch to aflibercept resulted in mean CRT resolution by 59.9±80.2 µm after the loading phase and by 61.3±102.9 µm at the study end point. Anatomical response to aflibercept switch was found in 34 of 41 eyes (83%) after the loading phase, and in 32 of 41 eyes (78%) at the study end point. BCVA improvement was 0.08±0.13 decimals in 26 of 41 eyes (63%) after the loading phase, and 0.04±0.17 decimals in 17 of 41 eyes (41%) at the study end point. The mean treatment interval of aflibercept was 8.0±2.2 weeks at the study end point. Conclusion: Regardless of impressive anatomical outcomes of aflibercept switch, functional response was modest for most of the study eyes at long term. Keywords: aflibercept, anti-VEGF, bevacizumab, treat-and-extend regimen protocol, wet age-related macular degeneration